2(4x+4)=10x+6-2x+2

Simple and best practice solution for 2(4x+4)=10x+6-2x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4x+4)=10x+6-2x+2 equation:


Simplifying
2(4x + 4) = 10x + 6 + -2x + 2

Reorder the terms:
2(4 + 4x) = 10x + 6 + -2x + 2
(4 * 2 + 4x * 2) = 10x + 6 + -2x + 2
(8 + 8x) = 10x + 6 + -2x + 2

Reorder the terms:
8 + 8x = 6 + 2 + 10x + -2x

Combine like terms: 6 + 2 = 8
8 + 8x = 8 + 10x + -2x

Combine like terms: 10x + -2x = 8x
8 + 8x = 8 + 8x

Add '-8' to each side of the equation.
8 + -8 + 8x = 8 + -8 + 8x

Combine like terms: 8 + -8 = 0
0 + 8x = 8 + -8 + 8x
8x = 8 + -8 + 8x

Combine like terms: 8 + -8 = 0
8x = 0 + 8x
8x = 8x

Add '-8x' to each side of the equation.
8x + -8x = 8x + -8x

Combine like terms: 8x + -8x = 0
0 = 8x + -8x

Combine like terms: 8x + -8x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 3n-17=3+5n | | 4-5w=-2w | | -7Y+4=60 | | 25x=625 | | -3+4(1-3m)=-12(m-11) | | 16m^2-8m-3= | | y=3x^2+12x+7 | | X+10Y=47 | | ln(2x+3)=ln(2x-1) | | -7(v-5)=-7(v+8) | | 16=16H | | 2x^2-8x-80=0 | | 8t-18=38+t | | X+6+6x=41 | | -7(v-5)=-7 | | 100x^2-y^4= | | 20s+4=13c-10 | | 9(x+6)=-9(3+2x) | | 7m-15-10m=6 | | (3y+5)=(4y-10) | | 5x^2=2+3x | | 5w+6-w=2 | | 4x+6=2x^2 | | 5x^2+2=3x | | 0=9x^2-39x+24 | | 25+1.75x=10+3.25x | | 6=y^2+5y | | 125=.005s^2+1.1s | | 2p^2-13p-20= | | -x+6(6x+2)=-2+7(-4+11) | | 0.04(4-1)=0.03(-1+8)+0.04 | | h=40t-5t^2 |

Equations solver categories